2024
DOI: 10.3390/su16051882
|View full text |Cite
|
Sign up to set email alerts
|

Implications of a Climate-Smart Approach to Food and Income Security for Urban Sub-Saharan Africa: A Systematic Review

Nolwazi Z. Khumalo,
Melusi Sibanda,
Lelethu Mdoda

Abstract: Climate change presents a significant threat to humanity. It affects agriculture, food supply, and economic development. Urban agriculture (UA) is an alternate climate-smart approach to enhancing food and income security. The climate-smart agriculture (CSA) concept promises to lessen the effects of climate change. Nuanced research is critical to warrant food and income security. This review paper synthesises evidence through a systematic literature search to analyse the implications of CSA practices and climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
0
0
0
Order By: Relevance
“…The empirical study findings are in line with the perspective of Khumalo et al [96], according to whom CSA has a profound impact on how agriculture adapts to climate change and manages associated risks. Promoting sustainable agricultural practices and innovative technologies, CSA can enhance farmers' adaptability to extreme weather conditions and contribute to reducing GHG in the agricultural sector [96]. This finding has significant implications for food security and global sustainability, as it helps protect natural resources and improve the resilience of food systems to impending climate change.…”
Section: Research Results Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The empirical study findings are in line with the perspective of Khumalo et al [96], according to whom CSA has a profound impact on how agriculture adapts to climate change and manages associated risks. Promoting sustainable agricultural practices and innovative technologies, CSA can enhance farmers' adaptability to extreme weather conditions and contribute to reducing GHG in the agricultural sector [96]. This finding has significant implications for food security and global sustainability, as it helps protect natural resources and improve the resilience of food systems to impending climate change.…”
Section: Research Results Discussionsupporting
confidence: 87%
“…These findings are consistent with previous research, such as that of Mizik [6], which has shown that agricultural production can be an essential factor in determining GHG. Moreover, Khumalo et al [96] have emphasized that CSA can have a significant impact on GHG, suggesting that more efficient and innovative agricultural practices could contribute to their reduction. The empirical study findings are in line with the perspective of Khumalo et al [96], according to whom CSA has a profound impact on how agriculture adapts to climate change and manages associated risks.…”
Section: Research Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation